Attracting medical school graduates to residency programs in remotely located hospitals: the challenge lies beyond financial incentives - Shalev Fried; Ofira Zloto; Avia Doron; Zeev Feldman; Alexey Belinsky; Gad Segal; Yael Frenkel-Nir; Arnon Afek (BMC, 2024)
Abstract Background Recruitment to residency programs in hospitals located in other than major hubs ("remotely located") is a challenge in many countries. In 2011, the Israeli Ministry of Health launched a 10-year financial incentive to encourage physicians to enroll in residency programs in such hospitals. Nearly 1 billion New Israeli Shekels (260 million US$) were invested in that program which had only limited success. As a new physician association's collective agreement is impending, we aimed to measure the effectiveness of selected incentives in attracting medical school graduates to residencies in remotely located hospitals. Methods This study included Israeli medical students in their final year of medical school. We used an online questionnaire with multiple-choice demographic questions and a 5-point Likert scale to gauge the effect of various incentives on their preference for residency location. Results Between July and November 2022, 522 students responded (405 studied in Israeli medical schools [out of 705 students] and 117 in foreign medical schools [out of 1936 students]). Forty-two percent had at least one clerkship in a remotely located hospital, and 24% had included at least one remotely located hospital among their top five choices for internship. Only 13% reported that they prefer a residency program in those institutions. The incentive selected by students as most persuasive was government assistance in acceptance to and financial support for a fellowship abroad, followed by a financial grant and fewer on-call hours. Only 7% of the students indicated that no incentive would influence them to choose a remotely located hospital for their residency training. Medical education in a remotely located university and the choice of at least one remotely located hospital among the top five choices for internship were significantly associated with positive incentive receptivity, whereas male sex and older age were associated with negative receptivity. Conclusion This study on the attitudes of Israeli medical school graduates toward incentives aimed at attracting them to residencies in remotely located institutions revealed that career development opportunities and assistance in obtaining fellowships might influence their choice.